PENGARUH LATIHAN OTOT LENGAN TERHADAP TEKNIK SMASH BULUTANGKIS UNTUK ANAK SMA - Mochamad Budi Syahril Romadon; Hana Astria Nur (STKIP Subang, 2025)
This study aimed to examine the effect of arm muscle training on the smash technique of badminton extracurricular students at SMA Negeri 1 Ciwaru. The research employed an experimental method with a one-group pretest–posttest design. The population consisted of all 21 badminton extracurricular students at SMA Negeri 1 Ciwaru during the 2024–2025 academic year. Data were collected through a smash technique test conducted in the field, and analyzed using a paired t-test. The results revealed a significant effect of arm muscle training on students’ smash technique. The average pretest score was 15.29, while the average posttest score was 19.10, indicating an improvement of 3.81 points. This shows that arm muscle training had a positive impact on the smash technique of badminton extracurricular students at SMA Negeri 1 Ciwaru